The effect of acute aerobic exercise on arterial stiffness in individuals with different body fat percentages: A cross-sectional study - Huang, Zegui; Chen, Guanzhi; Wang, Xianxuan; Zang, Yiran; Yue, Qing; Cai, Zefeng; Ding, Xiong; Chen, Zekai; Cai, Zhiwei; Wu, Kuangyi; Zheng, Huancong; Wu, Weiqiang; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Body fat percentage were positively correlated with arterial stiffness, but the acute change in arterial stiffness after aerobic exercise in individuals with different body fat percentages remains unclear. This study was aimed to determine the effect of acute aerobic exercise on arterial stiffness in individuals with different body fat percentages. Methods Individuals who both participated in the seventh survey of the Kailuan study and the fifth iteration of National Physical Fitness Monitoring were enrolled in our study. All participants underwent measurement of brachial–ankle pulse wave velocity, blood pressure, and heart rate before and after a two-stage load test on cycle ergometry. Additionally, the generalized linear model was established to analyse between-group differences of the change in brachial–ankle pulse wave velocity before and after exercise for individuals with different body fat percentages. Results The participants (N=940, 36.8±7.7years old, all male) were divided into: Q1 10.0~19.3%, Q2 19.3%~23.3%, Q3 23.3%~27.1% and Q4 27.1~37.7% by body fat percentage quartile. Overall, after exercise, brachial–ankle pulse wave velocity decreased significantly (before, 1375.1±209.1; after, 1341.5±208.0cm/s; p<0.01). After adjusting for confounding factors, the generalized linear model showed that the β values and 95% confidence interval (CI) of Q1, Q2 and Q3 groups were −38.1 (95% CI: −57.3, −19.0), −8.5 (95% CI: −25.8, 3.7), -3.7 (95% CI: −20.5, 13.0), respectively, when compared with Q4. For an increase in body fat percentage by one standard deviation (5.8%), β=14.5 (95% CI: 7.3, 21.6). Similar results were obtained in sensitivity analyses. Conclusions Acute aerobic exercise had a positive effect on the arterial stiffness of adults with different body fat percentages. Compared with individuals with high body fat percentages, the arterial stiffness of people with low body fat percentages had significant reduction after exercise.